APLIKASI TEKNOLOGI MOREA PLUS DALAM UPAYA MENINGKATKAN PRODUKTIVITAS SAPI BALI DI DESA BEBANDEM KARANGASEM - NI M. WITARIADI; P. ARI ASTAWA DAN NI (Buletin Udayana Mengabdi, 2008)
ABSTRACT. The activity of this community service aimed to introduce the principles and practice of using morea plus for increase the productivity of Bali cattle. The community service was carried out at Balai Banjar Tiingan Tengah, Bebandem, Karangasem on 2 Septembre 2007. The method used in this activity were discussion and demontration base on using morea plus for productivity increase of Bali cattle. It can be concluded that the response of the farmers to this activity was very high. All of the 30 members of the Gerembeng group of farmers who have been invited were come to the conducted meeting. The response of the farmers during demontration as well as during discussion was also high enough which indicated by the member and the quality of the questions from the farmers during the times being.